Right to be Forgotten vs. Public Information Disclosure to Public Officials in Indonesia - Bertha Cahyadewi; Wiwik Afifah (Mimbar Keadilan, 2026)
The advancement of information technology, which renders digital footprints permanent, has generated new problems in the protection of personal data, including for public officials who possess narrower privacy boundaries than private citizens. Research aims to explore the potential conflicts between the right to be forgotten and long-standing principle of transparency in Article 28F of the 1945 Republic of Indonesia's Constitution. Additionally, this paper looks at which public servants should be protected by the Right to Forget Law under Indonesian national laws or administrative regulations. This research deals with the difference between Indonesian National Laws for public servants and the right to be forgotten. It also discusses laws from “Republic of Indonesia No. 19/2016 Electronic Information Transactions Law of Republic of Indonesia No. 14/2008 Disclosure of Public Information Laws”. EU policy as well as the direction taken in member states such as France. The findings of the research show that the applicability of the Right to be Forgotten for public servants cannot be in an absolute form since information about their tasks of offices, track records, alleged ethical or legal violations, and actions that have an impact on the public is information that must remain accessible as part of public accountability. Additionally, this research reveals discrepancies in the court's and the Information Commission's authority when it comes to responding to information removal requests, which may lead to jurisdictional disputes.  In conclusion, the public interest must be considered when evaluating any use of the Right to be Forgotten by public officials. Considering the proportionality principle and regulatory harmonization is required to sustain transparent and accountable government by ensuring the proper finding a balance between protecting people's privacy and giving the public the right to know.